Type I Jejunal Atresia in Identical Twins: A Rare Occurrence - Amrollah Salimi; Shervin Rashidinia; Seyed Shahin Eftekhari; Mahsa Besharati; Sara Shahmoradi (EL-Med-Pub, 2017)
Jejunoileal atresia is of familial and non-familial in origins and classified into four different types. We herein report a rare occurrence of type I jejunal atresia in identical twins who were presented with neonatal intestinal obstruction. This report points towards common etiology of atresia in our cases and factors more than vascular accident appear to be involved.